An Intraoperative Rescue Procedure for the Protruding Premaxilla in the Repair of Complete Bilateral Cleft Lip: Rapid Premaxillary Molding. (February 2021) - Chung, Kyung Hoon; Sato, Nobuhiro; Chou, Pang-Yun; Lo, Lun-Jou
Background: Primary reconstruction of complete bilateral cleft lip and palate (BCLP) with protruding premaxilla in one-stage surgery is challenging because of the tension on muscle repair. Such patients are also common in the developing countries. For this condition, we have applied intraoperative "rapid premaxillary molding (RPM)" technique and obtained satisfactory results. Methods: We reviewed the data of patients with complete BCLP with protruding premaxilla applying intraoperative RPM including both our institution and cleft missions to developing countries in the past 20 years. Selection criteria were patients receiving either no or insufficient preoperative molding presenting with significant protruding premaxilla, had consecutive follow-ups after surgery. To perform this technique, the surgeon holds the patient's face with both hands and compresses the protruding premaxilla with both thumbs. An intermittent but stable backward pressure is applied to the premaxilla until the segment is gradually flexible. Repeated compression is performed prior to tying the muscle sutures, at which time the premaxilla is retro-positioned and aligned with the lateral maxillary segments. Pre- and postoperative data were evaluated. Results: We have treated a total of 60 patients with complete BCLP with protruding premaxilla applying intraoperative RPM. All patients tolerated the operations and there were no major intra- and postoperative complications including lip dehiscence and vomer fracture. All of them had satisfactory results such as adequate muscle repair and symmetry of the lip and nostrils. Conclusion: The RPM is a reliable and valuable intraoperative adjunct procedure for patients with complete BCLP presenting the protrusive premaxilla.